The Effect of Steam Curing on the Early Compressive Strength of Glass Powder Concrete - Geovenerdy, Ravelino Hafizh; Bali, Ika; Sudjatmiko, Eddy Triyanto (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2023)
Glass bottle waste is non-biodegradable and concerns about its impact on the environment. One alternative is to use recycled glass bottle waste in a form of glass powder as a partial replacement for fine aggregate in concrete. This study compared the glass powder concrete containing 20% glass powder as a partial replacement for fine aggregate treated by steam curing to the normal concrete treated by immersion curing. To obtain a higher early strength, the glass powder concrete will be treated with steam curing method for total duration of 9 hours. The test results showed that glass powder concrete treated with steam curing experienced a significant increase of 40.7% in compressive strength at 1 day of age with a compressive strength of 7.84 MPa compared to normal concrete of 5.56 MPa, an increase of 57.0% at 3 days of age with a compressive strength of 16.88 MPa compared to normal concrete of 10.75 MPa, and an increase of 14.0% at 7 days of age with a compressive strength of 23.86 MPa compared to normal concrete of 20.94 MPa. The results of this study indicated that steam curing has the effect of increasing the early compressive strength of concrete at the age of 1, 3 and 7 days. In addition, the use of 20% glass powder as a partial replacement for fine aggregate can contribute to the utilization of non-biodegradable glass bottle waste.